Whole Blood Clot Lysis: Enhanced by Exposure to Autologous but not to Homologous Plasma - Beer, J H; Kläy, H P; Herren, T; Haeberli, A; Straub, P W (Thrombosis and Haemostasis, 1994)
A new phenomenon is described: Whole blood clots lyse faster in the plasma of the same donor than in another donor’s plasma. We have confirmed this finding in 68 healthy volunteers by a standardized, pairwise analysis and have found a mean difference in clot weights of 8.8 ± 0.99% (SEM, p<0.0001) after 6 h of urokinase-induced (200 U/ml) clot lysis. Nu difference was found in a group of 7 pairs of identical twins. Further analysis revealed that increasing concentrations of platelets in the plasma reduced the difference significantly but did not abolish it. A 1:1 mixture of autologous with homologous plasma reduced the autologous advantage by almost 50%, thus making an inhibitor unlikely. The absence of cellular components in clots of platelet- poor plasma resulted in the loss of the advantage after 2 h of lysis, but not in the early phase. We conclude that there is a clear advantage of autologous over homologous clot lysis. Potential mechanisms are discussed and include an increased affinity of enzymes for their substrates in a given individual.